2016
DOI: 10.1093/ecco-jcc/jjw153
|View full text |Cite
|
Sign up to set email alerts
|

The Economic Impact of the Introduction of Biosimilars in Inflammatory Bowel Disease

Abstract: The introduction of biosimilars for infliximab can be expected to have a major impact on the cost profile of IBD. The economic impact will depend on local pricing, procurement policies and the physician's willingness to switch patients to biosimilars.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
43
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(44 citation statements)
references
References 20 publications
0
43
0
1
Order By: Relevance
“…However only supported by indirect evidence, the nocebo effect can also lead to unnecessary cessation of biologic treatment, thereby altering IBD patients' outcomes in clinical practice and in clinical trials . The consensus group expressed concerns that the nocebo effect may also negatively impact on the cost‐savings of biosimilars, while the main objective of implementing biosimilars in IBD is economically driven . Indeed, the nocebo effect can cause physicians to discontinue what is otherwise an appropriate therapy, prompt attempts to treat patients with additional drugs because of adverse events, or result in supplementary patient clinic visits.…”
Section: Discussionmentioning
confidence: 99%
“…However only supported by indirect evidence, the nocebo effect can also lead to unnecessary cessation of biologic treatment, thereby altering IBD patients' outcomes in clinical practice and in clinical trials . The consensus group expressed concerns that the nocebo effect may also negatively impact on the cost‐savings of biosimilars, while the main objective of implementing biosimilars in IBD is economically driven . Indeed, the nocebo effect can cause physicians to discontinue what is otherwise an appropriate therapy, prompt attempts to treat patients with additional drugs because of adverse events, or result in supplementary patient clinic visits.…”
Section: Discussionmentioning
confidence: 99%
“…These drugs, used to treat rheumatoid arthritis (worldwide prevalence rate estimated at 0.5–1.0% of the population) and Crohn’s disease (estimated incidence rate 6.3/100,000 person-years) [17, 23, 24], showed the most substantial expenditure increase, with more than 250 times (25098.7%), accounting for one third of purchases since 2010. For this class, price was the main factor boosting expenditure.…”
Section: Discussionmentioning
confidence: 99%
“…Biosimilars, market competition, and price reductions improve the cost-effectiveness of biologic therapy in RA. In IBD, existing data support the potential for biosimilars to deliver cost savings and improve patient access to biologics [133,134], and cost-effectiveness analyses are expected to be continuously updated. The cost-effectiveness of early biologic treatment in IBD is also being explored [135], whereas a model extrapolating data from the CALM trial in CD showed that "tight control," using biomarkers to direct adalimumab treatment, was cost-effective versus standard clinical management over 2-and 5-year timeframes, with cost-effectiveness improving over time [136].…”
Section: Pharmacoeconomists' Perspective: Cost Of and Access To Biolomentioning
confidence: 99%